Synthesis of isoflavone derivatives of crown ethers - (:unkn) unknown (SPRINGER, 1998)
The crown ether derivatives of isoflavones have been prepared and characterized. 7,8-dihydroxyisoflavon prepared from pyrogallol and 4-methoxy phenylacetonitrile reacted with ditosylates or dichloride of polyglycols in K2CO2/DMF/H2O. The crown ether-isoflavon derivatives containing 3-6 oxygen member rings were prepared. The structure of the compounds were verified by elemental analysis, H-1-NMR, C-13-NMR, IR and Chemical Ionisation Mass Spectroscopy.
Keywords: macrocyclics; isoflavones; chromogenic compounds; COUMARIN